Lexical Choices and Ideology in Translation: A Case Study of ’The old Man and the Sea - Najafian, Maryam (Journal of Social and Development Sciences, 2011)
The present research aims at conducting a critical study of the novel ’The Old Man and the Sea’ written by Ernest Hemingway (1976) and its two translated versions in Persian; one rendered by Faramarzi (2006) the other by Shahin (1979). The researchers apply a comparative lexical analysis proposed by Newmark (1988) and Venuti (1995). An attempt has been made to reveal the ideology behind the original sample words and to show how translators and the effect thereof handle it. The data of this research consists of 10 ideological laden terms selected randomly among 45 words from the original text and the corresponding Persian translations. The results of this study suggest a significant difference between the two Persian translations and the original novel. It revealed that one of the translators has attempted to ’domesticate’ his translation while another has been attentive to ’foreignize’ it. As for implication, it seems necessary to note that translational decisions made by actual translators under different socio-cultural and ideological settings in real life and real situations should be considered. The perlocutionary consequences resulted from adoption of such decisions are of importance.